Differences in emotional and behavior reactions of employees with the constructive and destructive envy coping strategy in the workplace relationship - Mikelevich, Alena B. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The ambiguity of scientific interpretations of constructiveness and destructiveness of envy is analyzed. It is shown that constructive and destructive envy coping strategy is manifested primarily in the emotional and behavioral component of the response. The results of a comparative analysis of emotional and behavioral reactions of employees with a constructive and destructive coping strategy with envy in the service relationship are presented. It is noted that regardless of gender, employees with a constructive and destructive strategy of coping with envy in official relations have differences in the indicator of active aggression: among employees with a destructive strategy, it is significantly higher. For men and womenwith a high level of constructive strategy, there were no significant differences in emotional and behavioral responses. With a high level of destructive strategy, men have higher rates of joy than women.
Keywords: envy in working relationships; emotional reactions of employees; behavioral reactions of employees; envy coping in official relations; constructive coping strategy; destructive coping strategy